Which common indices of sclerophylly best reflect differencesin leaf structure? - Groom, Philip; Lamont, Byron (1999)
When describing the sclerophyllous nature of leaves, two indices are most commonly cited: fibre:protein ratio (FPR), better known as the Loveless sclerophylly index; and leaf mass per unit area (LMA), or its inverse, specific leaf area (SLA). Here, we assess the relative importance of these two indices in accounting for changes in leaf structure, the primary basis for variations in sclerophylly. FPR compares structural (i. e., lignin and cellulose [crude fibre]) to non-structural (i.e., protein = protoplasm) leaf material, on the basis that increasing sclerophylly is associated with a greater contribution of crude fibre and smaller contribution of protein to total dry weight. However, raising the crude fibre content is just one way of increasing sclerophylly, and a decrease in the nitrogen content (i. e., protein) does not contribute directly to the impression of leaf hardness. While FPR lacks a clear anatomical basis, it may provide a biochemical interpretation of sclerophylly. In contrast, LMA is the cross product of leaf thickness and leaf density, two (often independent) attributes that are linked to different components of a leaf’s anatomical/structural attributes. We show that FPR and LMA are often poorly correlated and conclude that LMA is a more useful measure of sclerophylly, especially when thickness and density are known.